Mycoplasma pneumoniae – modern data on the structure, molecular biology and epidemiology of the pathogen - Edelstein I.A. (Клиническая микробиология и антимикробная химиотерапия, 2023)
Mycoplasma pneumoniae is a common etiologic agent of respiratory tract infections and communityacquired pneumonia (CAP) in children and adults. Recently, much new data on this pathogen, its molecular biology, cytoadherence and epidemiology have been accumulated. This review describes in detail the features of the microorganism and the pathogenesis of the diseases caused, clinical manifestations, provides data on the epidemiology of the incidence of respiratory mycoplasmosis and CAP caused by this microorganism in the world, discusses the issues of asymptomatic carriage, considers the problems of laboratory diagnosis, antibiotic therapy and antibiotic resistance of the pathogen.